2017
DOI: 10.5455/medscience.2017.06.8654
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative anxiety on the incidence of perioperative bronchospasm: a prospective observational study

Abstract: Independently from the chronic anxiety disorder, patients could feel nervousness and anxiety due to surgical stress during preoperative period. Preoperative anxiety could lead to various complications owing to autonomous nerve system activation. We targeted to examine the effects of preoperative anxiety on bronchospasm. In the study, 20-50 years old ASA I patient to be given elective endoscopic urologic operations were included. Totally 124 patients were evaluated during preoperative period. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Anxiety may aggravate symptoms of reactive airway diseases [37]. A prospective observational study by Kocaturk and Oguz showed that preoperative anxiety increases the risk for the development of bronchospasm following anesthesia induction [38]. Our results indicate that anesthesia‐related preoperative anxiety positively correlates with postoperative pulmonary complications.…”
Section: Discussionmentioning
confidence: 60%
“…Anxiety may aggravate symptoms of reactive airway diseases [37]. A prospective observational study by Kocaturk and Oguz showed that preoperative anxiety increases the risk for the development of bronchospasm following anesthesia induction [38]. Our results indicate that anesthesia‐related preoperative anxiety positively correlates with postoperative pulmonary complications.…”
Section: Discussionmentioning
confidence: 60%
“…Every patient is known different levels of anxiety due to various aspects such as the previous experiences, personality characteristics, anesthetics and surgery types to be applied and the pain expectation after the surgery [6]. In addition to the negative effects of preoperative anxiety on vital findings, it was also reported that it extends the recovery period and the staying time in hospital and that it has negative effects on postoperative pain and on nausea and vomiting [5,7].…”
Section: Preoperative Anxiety Overviewmentioning
confidence: 99%
“…Studies have shown perioperative anxiety is associated with haemodynamic instabilities during induction, 5 increased risk of bronchospasm, 6 delayed extubation, and prolonged hospital stay. 7 Anxiety can also increase acute postoperative pain, 8,9 increase analgesic consumption, 7 and increase the risk of developing chronic postsurgical pain.…”
Section: Introductionmentioning
confidence: 99%